Biomechanical analysis of internal fixation system stability for tibial plateau fractures - Wei, Guoqiang; Niu, Xiaofen; Li, Yuan; Chang, Tingjie; Zhang, Jianfang; Wang, Haiyan; Li, Xiaohe; He, Yujie; Wang, Ruijiang; Tian, Fei; Xu, Yangyang (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Complex bone plateau fractures have been treated with bilateral plate fixation, but previous research has overemphasized evaluating the effects of internal fixation design, plate position, and screw orientation on fracture fixation stability, neglecting the internal fixation system’s biomechanical properties in postoperative rehabilitation exercises. This study aimed to investigate the mechanical properties of tibial plateau fractures after internal fixation, explore the biomechanical mechanism of the interaction between internal fixation and bone, and make suggestions for early postoperative rehabilitation and postoperative weight-bearing rehabilitation. Methods: By establishing the postoperative tibia model, the standing, walking and running conditions were simulated under three axial loads of 500 N, 1000 N, and 1500 N. Accordingly, finite element analysis (FEA) was performed to analyze the model stiffness, displacement of fractured bone fragments, titanium alloy plate, screw stress distribution, and fatigue properties of the tibia and the internal fixation system under various conditions. Results: The stiffness of the model increased significantly after internal fixation. The anteromedial plate was the most stressed, followed by the posteromedial plate. The screws at the distal end of the lateral plate, the screws at the anteromedial plate platform and the screws at the distal end of the posteromedial plate are under greater stress, but at a safe stress level. The relative displacement of the two medial condylar fracture fragments varied from 0.002–0.072 mm. Fatigue damage does not occur in the internal fixation system. Fatigue injuries develop in the tibia when subjected to cyclic loading, especially when running. Conclusion: The results of this study indicate that the internal fixation system tolerates some of the body’s typical actions and may sustain all or part of the weight early in the postoperative period. In other words, early rehabilitative exercise is recommended, but avoid strenuous exercise such as running.